An Ancillary CT Finding of Intrapulmonary Solitary Fibrous Tumor: A Case Report - Dongjun Lee; Ji Young Rho; Ah-Young Kwon (대한영상의학회지, 2017)
Intrapulmonary solitary fibrous tumor is extremely rare. A few reports have presented typical CT findings such as well-defined, variable—sized, heterogeneously or homogenously well-enhanced intrapulmonary nodules. We report herein a rare case of intrapulmonary solitary fibrous tumor that showed typical clinical and CT features, and we also provide an ancillary CT finding that shows a distinguishable tubular vascular structure within the nodule. The tubular vascular structure was conjoined to the proximal pulmonary vein. In this study, we highlight an ancillary CT finding reported for the first time for the diagnosis of a patient with intrapulmonary solitary fibrous tumor.